CRISPR Technology for Ocular Angiogenesis - Chung, Sook Hyun; Sin, Tzu-Ni; Ngo, Taylor; Yiu, Glenn (Frontiers in Genome Editing, 2020)
Among genome engineering tools, Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-based approaches have been widely adopted for translational studies due to their robustness, precision, and ease of use. When delivered to diseased tissues with a viral vector such as adeno-associated virus, direct genome editing can be efficiently achieved in vivo to treat different ophthalmic conditions. While CRISPR has been actively explored as a strategy for treating inherited retinal diseases, with the first human trial recently initiated, its applications for complex, multifactorial conditions such as ocular angiogenesis has been relatively limited. Currently, neovascular retinal diseases such as retinopathy of prematurity, proliferative diabetic retinopathy, and neovascular age-related macular degeneration, which together constitute the majority of blindness in developed countries, are managed with frequent and costly injections of anti-vascular endothelial growth factor (anti-VEGF) agents that are short-lived and burdensome for patients. By contrast, CRISPR technology has the potential to suppress angiogenesis permanently, with the added benefit of targeting intracellular signals or regulatory elements, cell-specific delivery, and multiplexing to disrupt different pro-angiogenic factors simultaneously. However, the prospect of permanently suppressing physiologic pathways, the unpredictability of gene editing efficacy, and concerns for off-target effects have limited enthusiasm for these approaches. Here, we review the evolution of gene therapy and advances in adapting CRISPR platforms to suppress retinal angiogenesis. We discuss different Cas9 orthologs, delivery strategies, and different genomic targets including VEGF, VEGF receptor, and HIF-1, as well as the advantages and disadvantages of genome editing versus conventional gene therapies for multifactorial disease processes as compared to inherited monogenic retinal disorders. Lastly, we describe barriers that must be overcome to enable effective adoption of CRISPR-based strategies for the management of ocular angiogenesis.